Gear specific catch rates and size structure of channel catfish in the Upper Mississippi River. (24th March 2021) - Gainer, Colby G.; Kim, Hae H.; Phelps, Quinton E.
Abstract: Channel catfish are important to the Mississippi River (i.e., ecologically, commercially, and recreationally). The dynamic rate functions (recruitment, growth, and mortality) of the population are important to proper management. However, different gears can produce varying estimates of these vital rates (e.g., size selectivity or age selectivity). We evaluated the effectiveness of three commonly used gear types for sampling channel catfish. Sampling was completed following United States Army Corps of Engineers' Long‐Term Resource Monitoring (LTRM) element sampling protocol; pulsed direct current daytime electrofishing, baited 37 mm hoop nets (large hoop net), baited 18 mm hoop nets (small hoop net), and a tandem hoop net set that included one large and one small hoop net. A total of 65, 222 channel catfish were collected from 1993 to 2017. Channel catfish catch rates were lowest using daytime electrofishing and large hoop nets, while tandem hoop nets and small hoop nets had higher catch per unit effort (CPUE). Furthermore, tandem hoop nets collected a broader size distribution of channel catfish in comparison to daytime electrofishing, large hoop nets, and small hoop nets. As such, we recommend that tandem hoop nets should be used to evaluate channel catfish populations in the Upper Mississippi River as well as other riverine systems.